Retour sur les sociétés de montagne au Maghreb :fuqahā’ et soufis du Bilād Ghumāra (XIe-XVIIe siècles) à l’épreuve des réformes de la pratique religieuse - Mohamed Mezzine; Jacques/Jawhar Vignet-Zunz (Revue des Mondes Musulmans et de la Méditerranée)
The Rif mountains of Morocco still occupies a place of choice in the history books and even in theʿulamā’ milieu of the Qarawiyin in Fez. Names like those of Ibn Mashīsh, al-Habtī and Ibn ʿArdūn continue to feed a medieval historical tradition still alive today. These names bring us back to a time when the Ghmara country, as it was called at the time, was a cultural center that rivaled the city of Fez. Ibn Mashīsh and his disciple al-Shādhilī, both initiators of the famous ṭarīqa shādhiliyya, started from this mountain a religious reform movement that had a tremendous following among mountain populations, such as those of the throughout Morocco. On the other hand, the Ghmara fuqahā' , gatekeepers between ulamā’ and the common people, were trying to explain the Islamic standards to people who barely knew Arabic. The fewer ʿulamā' of the Jbel, more versed in legal and religious knowledge, shared between the network of the Andalusian religious science before 1492 and that of Fez, worked to shape the Maliki thought and to build it according to the requirements of their moutainous environment. To understand this phenomenon, this paper aims to follow the trajectories of the main reformers of awliyā’ Sufis and principal holders of knowledge (ʿulamā’), and to measure the impact of these attempts to reform Ghmara society.